P‐33: Color Classification of Images using Categorical Color Database. Issue 1 (May 2016) - Kumakura, Akihisa; Hamano, Toshiya; Ishikawa, Tomoharu; Ayama, Miyoshi
Abstract : Color classification using a pixel distribution criteria based on the categorical color database was done, and the adequateness of the criteria was examined by color naming experiment. Fifteen color categories were employed. For the category groups of "red", "green", and "blue", the criteria as well as the categorical database look fairly good, but still to be modified. Observers tend to label color names of main object in the image regardless of the pixel percentage. For some category groups, modification of categorical color database seems to be necessary.